Factors Influencing Bank Muamalat's Profitability With Non-Performing Financing As Moderators - Syarif, Magfira; Majid, Jamaluddin; Asse, Ambo; Sapa, Nasrullah Bin (Jurnal Ar-Ribh, 2023)
The research objective was to determine the effect of the capital adequacy ratio, financing to deposit ratio, and third party funds on profitability with non-performing financing as a moderating variable. This type of research is quantitative using secondary data processed through SPSS. The results of this study indicate that the capital adequacy ratio and the financing to deposit ratio have a significant effect on profitability but third party funds have no effect on profitability. Meanwhile, non-performing financing is not able to moderate the relationship between the capital adequacy ratio, financing to deposit ratio, and third party funds to profitability